The Effects of Short-Term Administration of Weight Reducing Herbal Drug (Mehzileen) on Serum Enzymes in Common Rabbits - Hasan, Ruqaiya; Javaid, Aisha; Fatima, Saqiba (Journal of Basic & Applied Sciences, 2012)
In the present study the weight reducing herbal drug, Mehzileen administered orally to common rabbits Oryctolagus cuniculus in a daily dose of 20 mg/ Kg body weight for 27 days. Blood samples drawn on day 0, 3, 7, 10 and 27 respectively were used to measure serum enzymes Aspartate Amino Transferase (AST) and Alanine Amino Transferase (ALT).Both the enzymes showed reduction in the early period of drug administration then started to elevate from day 10 of treatment. However AST remained significantly lower (p< 0.05) in test animals, while ALT continued to rise with slightly lower levels than initial concentrations at the end of experiment. These alterations in the AST and ALT levels suggest that major ingredients of the herbal drug used, probably interfere the metabolic activities of liver parenchyma and hepatocytes respectively